Mass treatment of trachoma with azithromycin 1.5% eye drops in the Republic of Cameroon: feasibility, tolerance and effectiveness. Issue 2 (18th August 2009) - Huguet, P; Bella, L; Einterz, E M; Goldschmidt, P; Bensaid, P
Abstract : Aims: An epidemiological study carried out in 2006 indicated a high prevalence of blinding trachoma in the Kolofata Health District, Far North Region, Republic of Cameroon. As a result, the national blindness control programme of Cameroon instituted a trachoma elimination programme using the SAFE strategy. Methods: A campaign to treat the entire district population with azithromycin 1.5% eye drops was undertaken in February 2008. To measure the effectiveness of treatment on the prevalence of active trachoma, two epidemiological studies were conducted on a representative sample of children aged between 1 and 10 years. The first study was performed just prior to the treatment campaign and the second study was performed 1 year later. Results: The prevalence of active forms of trachoma (trachomatous inflammation—follicular (TF) + TF/trachomatous inflammation—intense (TI)) dropped from 31.5 (95% CI 26.4 to 37.5)% before treatment to 6.3 (95% CI 4.1 to 9.6)% 1 year after treatment—a reduction of nearly 80%. There were no reports of serious or systemic side effects. Tolerance was excellent and no treatment was interrupted. Conclusion: Mass treatment with azithromycin 1.5% eye drops is feasible, well tolerated and effective.